Mitigasi Risiko Siber Pada Kontrak Investasi Teknologi Digital Dalam Perspektif Hukum Bisnis - Burhanudin; Baiq Widiantari (Fakultas Hukum Universitas Nahdlatul Ulama Nusa Tenggara Barat, 2026)
This study aims to examine the construction of cyber risk mitigation regulations in digital technology investment contracts, analyze the role of contracts as instruments for risk allocation and control, and identify the legal implications of the absence or ambiguity of cyber risk mitigation clauses on the parties' responsibilities. This study uses a normative legal approach, utilizing legal interpretation, legal theory, and legal principles as a framework for understanding and assessing applicable norms. The results show that, first, the construction of cyber risk mitigation in digital investment contracts is based on the principles of freedom of contract, legal certainty, obligation responsibility, and good faith, which are realized through clear, measurable, and proportional contractual clauses. Second, contracts function effectively as instruments for cyber risk allocation and control, with risks allocated to the party with the greatest control, thus ensuring legal certainty and protecting the interests of the parties. Third, the absence or ambiguity of cyber risk mitigation clauses creates legal uncertainty, complicates proving responsibility, and increases the potential for disputes. Therefore, detailed and explicit clauses are a normative necessity to strengthen the accountability and effectiveness of contracts.